The role of interparticle heterogeneities in the selenization pathway of Cu–Zn–Sn–S nanoparticle thin films: a real-time study. Issue 27 (18th June 2015) - Carter, Nathaniel J.; Mainz, Roland; Walker, Bryce C.; Hages, Charles J.; Just, Justus; Klaus, Manuela; Schmidt, Sebastian S.; Weber, Alfons; Yang, Wei-Chang D.; Zander, Ole; Stach, Eric A.; Unold, Thomas; et al.
Abstract : Small (∼5 nm), Cu- and Sn-rich nanoparticles play a key role in initiating the growth of micrometer-sized Cu2 ZnSn(S, Se)4 grains. Abstract : Real-time energy dispersive X-ray diffraction (EDXRD) analysis has been utilized to observe the selenization of Cu–Zn–Sn–S nanoparticle films coated from three nanoparticle populations: Cu- and Sn-rich particles roughly 5 nm in size, Zn-rich nanoparticles ranging from 10 to 20 nm in diameter, and a mixture of both types of nanoparticles (roughly 1 : 1 by mass), which corresponds to a synthesis recipe yielding CZTSSe solar cells with reported total-area efficiencies as high as 7.9%. The EDXRD studies presented herein show that the formation of copper selenide intermediates during the selenization of mixed-particle films can be primarily attributed to the small, Cu- and Sn-rich particles. Moreover, the formation of these copper selenide phases represents the first stage of the CZTSSe grain growth mechanism. The large, Zn-rich particles subsequently contribute their composition to form micrometer-sized CZTSSe grains. These findings enable further development of a previously proposed selenization pathway to account for the roles of interparticle heterogeneities, which in turn provides a valuable guide for future optimization of processes to synthesize high quality CZTSSe absorber layers.